Utilization of Technology in Development Business Management in the Post-Pandemic Era - Rina; Akbar, Rizky Aulia; Wahyuni, Ulfia (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
So far in 2019, the COVID-19 pandemic has claimed many lives. Due to the pandemic, many people have lost their jobs due to massive layoffs, and many businesses have failed. This journal examines the application of technology to business development in the post-COVID-19 era. Consequently, the purpose of this study is to develop businesses following the pandemic by utilizing the transformation of digital marketing technology and the difficulties in an era in which many individuals have used technology and social media to develop their businesses. Plans to utilize technology via websites or social media as well as e-commerce applications circulating on multiple platforms include: (a) determining sales goals or target markets; (b) preparing captions that attract buyers' interest in the goods we will market; and (c) planning sales goals to be achieved and managing expenses and income. The methods of digital marketing that we wish to describe are: a) promoting through product videos that pamper buyers; and b) creating their own website with an aesthetically pleasing design so that many interested individuals desire to purchase.As anticipated for research purposes, the results of this study indicate that digital marketing can be utilized as a means of business development in the post-pandemic era.Through the use of technology, businesses are able to develop rapidly, and the information that can be accessed is accurate and quick, thereby expanding the scope of sales.